Development of a survey tool for assessing life traumas and barriers to HIV care in a center of excellence for HIV/AIDS in Appalachian Tennessee. Issue 4 (2nd October 2021) - Loudermilk, Elaine N.; White, Melissa; Turner, Emmitt; Jones, Morgan K.; Mamudu, Hadii M.; Bynum, Lisa; Underwood, Roxanne F.; Dotson, L. Susan; Adkins, James; Bohannon, Joy M.; Mathis, Stephanie M.; Foster, Kelly N.; et al.
Abstract: Introduction: A culturally competent survey currently does not exist to characterize the burden of Adverse Childhood Experiences (ACEs) among a HIV/AIDS population receiving care at a local Center of Excellence (COE). Methods: A qualitative study was conducted including 11 interviews involving opinions on national surveillance questions to develop a culturally competent survey. Purposive sampling, reactive probing, and analysis of transcribed interviews were completed using structured coding to determine which questions were kept, modified, or removed​ in the final survey. Results: The final 55-question survey contained more generalized ACE questions, topics pertaining to barriers to HIV care, and a list that patients could select from to indicate what they need to improve their HIV care. Conclusion: The final survey provided the opportunity to characterize the burden of ACEs at a COE. Future directions involve piloting the survey as a quality improvement tool with the goal of increasing retention rates through more individualized HIV care.